The Impact of Islamic Ethics-Based Leadership on Microenterprise Performance in Indonesia: An Analysis of Financial Inclusion, Business Ethics, and Innovation - Loso Judijanto; Sabil Mokodenseho; Ramli Semmawi; Syarifuddin Yusuf (Westscience Press, 2023)
In the context of Indonesian microenterprises, this study explores the complex interactions among financial inclusion, business ethics, innovation, and Islamic ethics-based leadership. The study uses a sample of 175 microenterprise owners and managers to investigate the structural links among these factors using a quantitative approach. The results show that Islamic ethics-based leadership, financial inclusion, innovation, and business ethics are significantly and favorably correlated. Innovation has a substantial positive link with Islamic Ethics-Based Leadership, whereas Business Ethics and Financial Inclusion show modest positive relationships. The study's findings advance knowledge of the variables impacting moral leadership in Indonesian microenterprises and have applications for managers and legislators who want to promote moral corporate conduct in the context of Islam.